Trend Moment Analysis of NTP for Food Crops and Horticulture in East Java Province - Hariri, Rifan (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The existence of food crops and horticultural crops is very important so it is necessary to see the level of welfare of farmers of food crops and horticultural crops. An indicator that is very often used to measure the level of welfare of farmers of food crops and horticultural crops is the farmer exchange rate or more commonly called NTP. This study uses time series data from January 2024 to March 2025. Data obtained from the Central Bureau of Statistics of East Java Province in 2025. Data analysis using the trend moment method. The results obtained show that in April 2025 the NTP for food crops was 97.27 and the NTP for horticultural crops was 139.76.